2017
DOI: 10.1113/jp273928
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrient restriction during pregnancy and lactation leads to impaired right ventricular function in young adult baboons

Abstract: Maternal nutrient restriction induces intrauterine growth restriction (IUGR), increasing later life chronic disease including cardiovascular dysfunction. Our left ventricular (LV) CMRI studies in IUGR baboons (8 M, 8 F, 5.7 years - human equivalent approximately 25 years), control offspring (8 M, 8 F, 5.6 years), and normal elderly (OLD) baboons (6 M, 6 F, mean 15.9 years) revealed long-term LV abnormalities in IUGR offspring. Although it is known that right ventricular (RV) function is dependent on LV health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 78 publications
5
39
0
Order By: Relevance
“…These data along with the changes to contractility proteins (PLB and Troponin I) in the present study may explain the emergence of dysfunction in the right ventricle after birth in the IUGR non‐human primate (Kuo et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These data along with the changes to contractility proteins (PLB and Troponin I) in the present study may explain the emergence of dysfunction in the right ventricle after birth in the IUGR non‐human primate (Kuo et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…A more moderate (30%) maternal nutrient restriction in the non‐human primate causes signs of both left and right ventricle dysfunction in the offspring, including a decreased ejection fraction, wall shortening and increased chamber volume as assessed using magnetic resonance imaging (Kuo et al . , b ). Interestingly, these two partner studies highlighted that right ventricular function was more severely impacted by maternal nutrient restriction than left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that overall heart function declines with ageing in the baboon (Kuo et al . a , b ), but no studies have reported normative declines across the life course.…”
Section: Introductionmentioning
confidence: 99%
“…In line with observations in human IUGR offspring, there are now elegant non‐human primate data derived from cardiac magnetic resonance imaging that reports IUGR also being associated with cardiac remodelling in young adult baboons (Kuo et al . ,b). Studies in rodent mammalian animal models have also reported that chronic fetal hypoxia can programme cardiac and vascular dysfunction in later life (Thompson & Weiner, ; Kim et al .…”
Section: Introductionmentioning
confidence: 99%